Exploring Potential Phytochemicals for Myasthenia Gravis Treatment: A Molecular Docking and ADME Analysis Approach - Neha Subhash Nilawad (International Journal of Molecular Biotechnological Research, 2024)
Objective: Muscle feebleness and exhaustion derived from a disruption in neuromuscular transference are hallmarks of the crippling autoimmune disease myasthenia gravis (MG). The drawbacks of the current MG therapy options are frequently partial efficacy and adverse effects. To investigate the potential of phytochemicals in MG control, in this work we integrated molecular docking with ADME (absorption, distribution, metabolism, and excretion) analysis using a computer method. We identified molecules exhibiting favorable interactions with key molecular targets implicated in MG pathophysiology, such as muscle-specific kinase (MuSK), nicotinic acetylcholine receptors (nAChRs), and acetylcholinesterase (AChE). Explore the natural substances called phytochemicals that are derived from plants and may have therapeutic uses in treating a variety of ailments, including autoimmune disorders. This has become more and more popular in the past few years. Methods: Theoretical Methodology: This study aims to explore the potential of phytochemicals from the Cassia fistula medicinal plant for the treatment of Myasthenia gravis (MG) through a multi-step computational approach. Firstly, the top five phytochemicals from Cassia fistula will be selected based on a literature review and computational screening. These compounds will then undergo molecular docking onto the active site of the muscle-specific kinase (MuSK) protein (PDB ID: 1LUF) using PyRx software to predict their binding affinities and interactions. Following this, ADME (absorption, distribution, metabolism, and excretion) analysis will be conducted to evaluate the pharmacokinetic properties of the docked compounds, including bioavailability and toxicity. To identify possible lead compounds for additional experimental validation, Biovia software will be used to visualize protein-ligand interactions. This integrated approach holds promise for the discovery of novel phytochemical-based therapeutics for MG treatment. Result: Molecular docking investigations indicated that Rhein, chrysophanic acid, aromadendrin, aloe emodin, and anthraquinone were in the ligands with the lowest binding affinities to the targeted proteins. Conclusion: In conclusion, we have effectively discovered phytochemicals with promise for treating Myasthenia gravis (MG) by our molecular docking and ADME analysis technique utilizing Biovia and PyRx. Using computational screening, we found phytochemicals with good pharmacokinetic characteristics and a substantial binding affinity to MG-related target proteins. These results demonstrate the possibility of using natural substances as MG treatment alternatives. To determine these compounds’ safety and efficacy and to prepare the way for the creation of novel MG therapies based on phytochemicals, more experimental validation of these compounds is necessary.
Keywords: ADME analysis; Myasthenia gravis; Phytochemicals; Precision medicine; molecular docking; neuromuscular transmission